The role of peptidoglycan hydrolases in the formation and toxicity of Pseudomonas aeruginosa membrane vesicles. Issue 1 (30th June 2022) - Chen, Yi-Chi; Kalawong, Ratchara; Toyofuku, Masanori; Eberl, Leo
Abstract: Bacterial membrane vesicles (MVs) have been reported to kill other bacteria. In the case of Pseudomonas aeruginosa the bactericidal activity has been attributed to an unidentified 26 kDa peptidoglycan (PG) hydrolase that is associated with MVs and gives rise to a lytic band on zymograms using murein sacculi as substrate. In this study, we employed a proteomics approach to show that this PG hydrolase is the AmphD3 amidase. The analysis of an amphD3 mutant as well as of an AmphD3 overexpression derivative revealed that this enzyme is not required for the bactericidal activity of P. aeruginosa MVs but is involved in cell wall recycling and thus protects the cell against PG damage. Another 23 kDa PG hydrolase, which we observed on zymograms of SOS-induced MVs, was identified as the endolysin Lys, which triggers explosive cell lysis but is shown to be dispensable for MV-mediated killing. We conclude that the lytic activities observed on zymograms do not correlate with the bactericidal potential of MVs. We demonstrate that P. aeruginosa MVs are enriched for several autolysins, suggesting that the predatory activity of MVs depends on the combined action of different murein hydrolases. Abstract : Peptidoglycan hydrolytic activities on zymograms do not correlate with the bacteriocidal potential of membrane vesicles.